The earlier Neolithic in Cyprus: recognition and dating of a Pre-Pottery Neolithic A occupation - Manning, Sturt W.; McCartney, Carole; Kromer, Bernd; Stewart, Sarah T. (Antiquity, 2010)
Intensive survey and initial excavations have succeeded in pushing back the Neolithic human occupation of Cyprus to the earlier ninth millennium cal BC. Contemporary with PPNA in the Levant, and with signs of belonging to the same intellectual community, these were not marginalised foragers, but participants in the developing Neolithic project, which was therefore effectively networked over the sea.
Online publiziert am 02. Januar 2015
Gesehen am 04.05.2023